Variational methods to second-order Dirichlet boundary value problems with impulses on the half-line - Djibaoui, Meriem; Moussaoui, Toufik (CUBO, A Mathematical Journal, 2022)
In this paper, the existence of solutions for a second-order impulsive differential equation with a parameter on the half-line is investigated. Applying Lax-Milgram theorem, we deal with a linear Dirichlet impulsive problem, while the non-linear case is established by using standard results of critical point theory.